Inquiry-based learning on the cloud - Mikroyannidis, Alexander; Okada, Alexandra; Correa, Andre [UNESP]; Scott, Peter (My University, 2016)
Cloud Learning Environments (CLEs) have recently emerged as a novel approach to learning, putting learners in the spotlight and providing them with the cloud-based tools for building their own learning environments according to their specific learning needs and aspirations. Although CLEs bring significant benefits to educators and learners, there is still little evidence of CLEs being actively and effectively used in the teaching and learning process. This chapter addresses this issue by introducing a European initiative called weSPOT (Working Environment with Social, Personal and Open Technologies for Inquiry-based Learning) for supporting and enhancing inquiry-based learning in STEM education via a cloud-based inquiry toolkit. The chapter presents evidence of using this toolkit within a case study that investigates how a secondary education community of students / co-learners selects information sources on the web and identifies factors associated with the reliability of information sources during their collaborative inquiry (co-inquiry) project in online environments.